An antibacterial aluminum foil material and its preparation method and application
By fixing Ag/Cu metal particles in TiO2/ZnO deposited cross-linked coated montmorillonite, and preparing them into a paint and spin-coated on aluminum foil, the problem of easy shedding and poor durability of the antibacterial layer of the existing antibacterial aluminum foil material is solved. It achieves long-term antibacterial performance and safe and non-toxic effects.
Patent Information
- Application Number
- CN202310805521.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-03
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-07-03
AI Technical Summary
The antibacterial layer of the existing antibacterial aluminum foil packaging materials is prone to fall off, has poor durability, and has high metal ion release rate, which has toxicity problems.
The Ag/Cu metal particles were fixed in TiO2/ZnO deposition cross-linked coated montmorillonite and added to polysiloxane to prepare a coating, and evenly spin-coated on aluminum foil to form an antibacterial layer.
It realizes the long-term antibacterial properties of antibacterial aluminum foil materials, which are safe and non-toxic, and improves the mechanical properties of aluminum foil, avoids coating shedding and film cracking, and has a long service life.
Smart Images

Figure BDA0004317580420000131 
Figure BDA0004317580420000161
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum foil materials, and in particular to an antibacterial aluminum foil material and a preparation method and application thereof. Background Art
[0002] Aluminum foil is widely used in food, beverages, cigarettes, medicines, household products, etc. due to its excellent properties, and is usually used as its packaging material. The development prospects of aluminum foil packaging are very broad; composite aluminum foil material packaging has the advantages of high barrier performance, light weight, UV resistance, long shelf life at room temperature, etc., and is increasingly widely used in the packaging of convenience foods, cooked foods, medicines, etc. In recent years, due to technological progress, human concern for health and enhanced environmental awareness, packaging materials are developing in a safer, more comprehensive and pollution-free direction. The world's packaging materials are developing in a diversified, diversified, safety-oriented and environmentally friendly direction. However, current packaging materials usually do not have a sterilization function, which makes it easy for bacteria to invade food or medicines, causing food or medicines to deteriorate, breed bacteria, and threaten people's health and safety.
[0003] Chinese patent application CN107379655A discloses an antibacterial polyester / aluminum foil composite packaging film and a preparation method thereof, the preparation method comprising: 1) pre-treating the aluminum foil, and then placing it in an electroplating solution for electroplating so that an electroplating layer is formed on the surface of the aluminum foil to obtain an electroplated aluminum foil; 2) mixing polyester, ethylene-methacrylic acid copolymer, calcium oxide, vaseline, hydroquinone, rosin, diphenylsilanediol, ephedra, bupleurum, burdock, notopterygium and angelica to obtain a mixed material; 3) applying an adhesive to one side of the electroplated aluminum foil, followed by drying to form an adhesive layer, and then hot-pressing the mixed material on top of the adhesive layer to form a polyester layer to obtain an antibacterial polyester / aluminum foil composite packaging film; wherein the pH of the electroplating solution is 4-5.5, and contains Ag. + , Pd 2+ , Cu 2+ and Ti 4+ , the electroplating anode contains Ag, Pd, Cu and Ti. The antibacterial polyester / aluminum foil composite packaging film has excellent antibacterial properties, and the preparation method has the advantages of simple process and easy availability of raw materials. However, the antibacterial layer of the antibacterial polyester / aluminum foil composite packaging film prepared by one-step electroplating and coating is easy to fall off, the antibacterial durability is poor, and the high metal ion release rate will cause certain toxicity. Summary of the invention
[0004] The purpose of the present invention is to propose an antibacterial aluminum foil material and a preparation method and application thereof. The coating is prepared by adding Ag / Cu metal particles to fix TiO2 / ZnO deposited cross-linked coated montmorillonite into polysiloxane and evenly spin-coated on the aluminum foil, so that the prepared antibacterial aluminum foil material has excellent long-lasting antibacterial performance and is safe and non-toxic, and can improve the mechanical properties of the aluminum foil. At the same time, the coating can avoid cracks during the heating treatment process, and there is almost no problem of film cracking, no coating shedding, good uniformity, long service life, and broad application prospects.
[0005] The technical solution of the present invention is achieved in this way:
[0006] The invention provides a preparation method of an antibacterial aluminum foil material. The method comprises the following steps: acid-treating montmorillonite, wrapping a cross-linked chitosan-alginate material, adding the material into a Ti-Zn sol, heating and drying, calcining, and ball milling to obtain a TiO2 / ZnO deposited cross-linked coated montmorillonite, adding the material into a solution containing copper ammine ions and silver ammine ions, adding glucose for reduction reaction, depositing Ag and Cu metal particles, uniformly mixing the material with polysiloxane, a silane coupling agent, an additive and an organic solvent to obtain an antibacterial coating, uniformly spin-coating the material on an aluminum foil to form an antibacterial layer, and heating and baking to solidify the material to obtain the antibacterial aluminum foil material.
[0007] As a further improvement of the present invention, the following steps are included:
[0008] S1. Pretreatment of montmorillonite: adding montmorillonite to an acid solution, stirring the reaction, filtering, washing, and drying to obtain pretreated montmorillonite;
[0009] S2 chitosan - alginate cross-linked coating: chitosan was dissolved in a dilute acid solution, the pretreated montmorillonite obtained in step S1 was added, stirred and mixed evenly, alginate was added, stirred to react, filtered, washed, and dried to obtain a cross-linked coated montmorillonite;
[0010] S3. Preparation of Ti-Zn sol: dissolve tetrabutyl titanate and zinc acetate in an ethanol aqueous solution, adjust the pH value of the solution to acidic, stir and react to obtain Ti-Zn sol;
[0011] S4. Preparation of TiO2 / ZnO deposition cross-linked coated montmorillonite: adding the cross-linked coated montmorillonite obtained in step S2 to the Ti-Zn sol obtained in step S2, stirring and mixing evenly, heating and drying, calcining, and ball milling to obtain TiO2 / ZnO deposition cross-linked coated montmorillonite;
[0012] S5. Preparation of copper-silver ammonia complex ion solution: Dissolve a soluble copper salt and a soluble silver salt in water, add aqueous ammonia until the precipitate just disappears, and obtain a copper-silver ammonia complex ion solution;
[0013] S6. Preparation of Ag / Cu metal particles fixed TiO2 / ZnO deposition cross-linked coated montmorillonite: adding the TiO2 / ZnO deposition cross-linked coated montmorillonite obtained in step S4 to the copper-silver ammine ion solution obtained in step S5, adding glucose, heating and stirring to react, filtering, washing, and drying to obtain Ag / Cu metal particles fixed TiO2 / ZnO deposition cross-linked coated montmorillonite;
[0014] S7. Preparation of antibacterial aluminum foil material: polysiloxane, silane coupling agent, Ag / Cu metal particles fixed TiO2 / ZnO deposited cross-linked coated montmorillonite obtained in step S6, additives and organic solvent are mixed evenly to obtain an antibacterial coating, which is evenly spin-coated on aluminum foil to form an antibacterial layer, and heated and baked to cure to obtain an antibacterial aluminum foil material.
[0015] As a further improvement of the present invention, the acid solution in step S1 is a 2-4 mol / L nitric acid or sulfuric acid solution, and the stirring reaction time is 20-30 min; the dilute acid solution in step S2 is a 1-1.5wt% acetic acid or hydrochloric acid solution, the mass ratio of the chitosan, pretreated montmorillonite, and alginic acid is 10-12:25-30:5-10, the stirring reaction temperature is 40-45°C, and the time is 50-60 min.
[0016] As a further improvement of the present invention, the mass ratio of tetrabutyl titanate and zinc acetate in step S3 is 15-20:7-12, the concentration of the ethanol aqueous solution is 50-70wt%, the pH value of the adjusted solution is 5-6, and the stirring reaction time is 40-60min.
[0017] As a further improvement of the present invention, the mass ratio of the cross-linked coated montmorillonite and the Ti-Zn sol in step S4 is 15-20:30-50, the heating and drying temperature is 105-110°C, the time is 1-2h, the calcination temperature is 400-600°C, the time is 2-3h, and the ball milling time is 1-2h.
[0018] As a further improvement of the present invention, the soluble copper salt in step S5 is selected from at least one of copper chloride, copper sulfate, and copper nitrate, the soluble silver salt is silver nitrate, and the mass ratio of the soluble copper salt to the soluble silver salt is 5-7:17-20; the mass ratio of the TiO2 / ZnO deposition cross-linked coated montmorillonite, copper-silver ammine complex ion solution, and glucose in step S6 is 10-15:30-40:5-7, and the heating and stirring reaction time is 85-95°C for 1-2h.
[0019] As a further improvement of the present invention, the silane coupling agent in step S7 is selected from at least one of KH550, KH560, KH570, KH580, KH590, KH602, and KH792, preferably, a mixture of KH550 and KH602, with a mass ratio of 3-5:7, the additives include a defoamer and a leveling agent, preferably, dimethylpentylamide and hexadecyl alcohol, with a mass ratio of 2-3:1-2, and the organic solvent is selected from ethyl acetate. At least one of ester, methyl acetate, butyl acetate, acetone, methyl ethyl ketone, petroleum ether, ethyl ether, and ethanol, the mass ratio of the polysiloxane, the silane coupling agent, the Ag / Cu metal particles fixed TiO2 / ZnO deposited cross-linked coated montmorillonite obtained in step S6, the additive and the organic solvent is 12-15:1-2:4-6:1-2:30-40, the thickness of the antibacterial layer is 1-2mm, the temperature of the heating and baking curing is 100-110°C, and the time is 1-2h.
[0020] As a further improvement of the present invention, the present invention specifically comprises the following steps:
[0021] S1. Pretreatment of montmorillonite: adding montmorillonite to 2-4 mol / L nitric acid or sulfuric acid solution, stirring the reaction for 20-30 min, filtering, washing, and drying to obtain pretreated montmorillonite;
[0022] S2. Chitosan-alginate cross-linked coating: 10-12 parts by weight of chitosan are dissolved in 100 parts by weight of 1-1.5wt% acetic acid or hydrochloric acid solution, 25-30 parts by weight of the pretreated montmorillonite prepared in step S1 are added, stirred and mixed uniformly, 5-10 parts by weight of alginate are added, the reaction is stirred at 40-45°C for 50-60min, filtered, washed, and dried to obtain a cross-linked coated montmorillonite;
[0023] S3. Preparation of Ti-Zn sol: 15-20 parts by weight of tetrabutyl titanate and 7-12 parts by weight of zinc acetate are dissolved in 100 parts by weight of a 50-70wt% ethanol aqueous solution, the pH value of the solution is adjusted to 5-6, and the reaction is stirred for 40-60 minutes to obtain a Ti-Zn sol;
[0024] S4. Preparation of TiO2 / ZnO deposition cross-linked coated montmorillonite: add 15-20 parts by weight of the cross-linked coated montmorillonite obtained in step S2 to 30-50 parts by weight of the Ti-Zn sol obtained in step S2, stir and mix evenly, heat to 105-110°C and dry for 1-2h, calcine at 400-600°C for 2-3h, and ball mill for 1-2h to obtain TiO2 / ZnO deposition cross-linked coated montmorillonite;
[0025] S5. Preparation of copper - silver ammine ion solution: 5-7 parts by weight of a soluble copper salt and 17-20 parts by weight of a soluble silver salt are dissolved in 100 parts by weight of water, and 22-25wt% of aqueous ammonia is added dropwise until the precipitate just disappears to obtain a copper - silver ammine ion solution;
[0026] S6. Preparation of Ag / Cu metal particles fixed TiO2 / ZnO deposition cross-linked coated montmorillonite: add 10-15 parts by weight of the TiO2 / ZnO deposition cross-linked coated montmorillonite obtained in step S4 to 30-40 parts by weight of the copper-silver ammine ion solution obtained in step S5, add 5-7 parts by weight of glucose, heat to 85-95°C, stir to react for 1-2h, filter, wash, and dry to obtain Ag / Cu metal particles fixed TiO2 / ZnO deposition cross-linked coated montmorillonite;
[0027] S7. Preparation of antibacterial aluminum foil material: 12-15 parts by weight of polysiloxane, 1-2 parts by weight of silane coupling agent, 4-6 parts by weight of Ag / Cu metal particles fixed TiO2 / ZnO deposited cross-linked coated montmorillonite obtained in step S6, 1-2 parts by weight of additives and 30-40 parts by weight of organic solvent are mixed evenly to obtain an antibacterial coating, and the coating is evenly spin-coated on aluminum foil to form an antibacterial layer with a thickness of 1-2 mm, heated to 100-110° C., and baked and cured for 1-2 hours to obtain an antibacterial aluminum foil material;
[0028] The silane coupling agent is a mixture of KH550 and KH602 with a mass ratio of 3-5:7; the chitosan, oxides, etc. on the Ag / Cu metal particles fixed TiO2 / ZnO deposition cross-linked coated montmorillonite material have a large number of hydroxyl structures, which are convenient for forming hydrogen bonds with the silane coupling agent with amino groups, thereby making the organic and inorganic materials stably composited to form a uniformly dispersed and uniform coating, so that the Ag / Cu metal particles fixed TiO2 / ZnO deposition cross-linked coated montmorillonite can be spin-coated on the aluminum foil surface evenly without agglomeration, while improving the adhesion performance of the coating on the aluminum foil surface, avoiding problems such as coating shedding and cracking, thereby exerting a stable antibacterial property.
[0029] The additives include dimethylpentylamide and hexadecyl alcohol in a mass ratio of 2-3:1-2.
[0030] The present invention further protects an antibacterial aluminum foil material obtained by the above-mentioned preparation method.
[0031] The present invention further protects an application of the antibacterial aluminum foil material in packaging materials.
[0032] The present invention has the following beneficial effects: The reason why the antibacterial layer of the present invention usually causes the death of bacteria and viruses is that the metal particles can release metal ions, such as Ag + , Cu 2+, with positive charge, while the cell membrane of bacteria, viruses and other microorganisms has negative charge. Under the action of Coulomb attraction, the two are combined together, and the metal ions take the opportunity to pass through the cell membrane and enter the cell. The protein in the cell coagulates and loses its activity under the action of heavy metal ions. Therefore, the cell cannot produce synthase for synthesizing DNA, and the cell dies due to the destruction of its proliferation ability. After the microorganism loses its activity, the metal ions are freed and a new round of sterilization is carried out, and the long-term sterilization effect is achieved over and over again.
[0033] Ag, TiO2 and ZnO in the antibacterial layer of the present invention have photocatalytic effects. These metal ions with photocatalytic effects activate oxygen molecules in the water and air system to generate hydroxyl radicals (-OH) and active oxygen ions (O 2- ). Under the action of these strong oxidants, the structures of proteins, glycosides and other substances in bacteria are destroyed, and their normal metabolic functions are disturbed, so they cannot proliferate normally and eventually die, thus achieving the purpose of antibacterial and bactericidal. Among them, under the photocatalytic action of ZnO, the main active oxygen substance H2O2 can be produced, and H2O2 can react chemically with membrane proteins to kill bacteria. At the same time, the photocatalytic material in the present invention has a relatively high heat resistance and can adapt to some harsh and demanding environments. However, since its application scenario must be exposed to ultraviolet light and there must be water and oxygen, the present invention is also combined with other antibacterial materials to achieve synergistic antibacterial effects.
[0034] The present invention firstly performs acid treatment on montmorillonite with antibacterial property and biocompatibility, and Si with four times coordination in the layer of montmorillonite is replaced by Al, and Al with six times coordination is replaced by Mg, Fe, etc., so as to generate negative charge. The acid treatment allows a large amount of H, Na, and Ca to be exchanged between the layers, and at the same time, a large amount of hydroxyl active groups are generated on the surface. This facilitates the subsequent replacement of ions in the multilayer structure of the montmorillonite with antibacterial metal ions, thereby loading a large amount of Cu, Ag, TiO2 and ZnO, and significantly improving the antibacterial property.
[0035] However, due to the large amount of silver ions deposited and well released, its antibacterial effect does not need to be worried, but often too much silver ions will lead to three problems: the toxicity of too high silver ions brings some safety problems; the second is that too much free silver ions easily discolor the appearance of the antibacterial material, and this mechanism will reduce the durability of the product and not take advantage of the long-term antibacterial effect. Therefore, after the montmorillonite is acid-treated, the present invention further cross-links chitosan and alginic acid, and the cations in the chitosan can attract each other with the anionic alginic acid to form a cross-linked structure, so that the carrier has a complex and multi-layer structure, which is not conducive to the large amount and rapid release of silver ions and copper ions, and plays a certain slow release effect, so as to facilitate the extension of the antibacterial time and the service life. The released metal ions will not cause toxicity. At the same time, the chitosan-alginic acid cross-linked structure formed also has good biological antibacterial performance, which can play a synergistic effect. At the same time, the coating prepared by the added Ag / Cu metal particles fixing TiO2 / ZnO deposition cross-linking coated montmorillonite can improve the mechanical properties, toughness, wear resistance and hardness of the aluminum foil.
[0036] The antibacterial aluminum foil material prepared by the present invention is prepared by adding Ag / Cu metal particles to fix TiO2 / ZnO deposited cross-linked coated montmorillonite into polysiloxane to form a coating which is evenly spin-coated on the aluminum foil, so that the prepared antibacterial aluminum foil material has excellent long-lasting antibacterial performance and is safe and non-toxic, while being able to improve the mechanical properties of the aluminum foil. At the same time, the coating can avoid cracks during the heating treatment process, and there is almost no problem of film cracking, good uniformity, long service life, and broad application prospects. DETAILED DESCRIPTION
[0037] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Montmorillonite was purchased from Shengfei Mineral Products Processing Plant in Lingshou County, 200 mesh, content>99%.
[0039] Example 1
[0040] This embodiment provides a method for preparing an antibacterial aluminum foil material, which specifically includes the following steps:
[0041] S1. Pretreatment of montmorillonite: montmorillonite was added to a 2 mol / L nitric acid solution, stirred for 20 min, filtered, washed, and dried to obtain pretreated montmorillonite;
[0042] S2. Chitosan-alginate cross-linked coating: 10 parts by weight of chitosan was dissolved in 100 parts by weight of 1wt% acetic acid solution, 25 parts by weight of the pretreated montmorillonite prepared in step S1 was added, stirred and mixed for 20 min, 5 parts by weight of alginate was added, stirred and reacted at 40 ° C for 50 min, filtered, washed, and dried to obtain a cross-linked coated montmorillonite;
[0043] S3. Preparation of Ti-Zn sol: 15 parts by weight of tetrabutyl titanate and 7 parts by weight of zinc acetate were dissolved in 100 parts by weight of a 50 wt% ethanol aqueous solution, the pH value of the solution was adjusted to 5, and the reaction was stirred for 40 minutes to obtain a Ti-Zn sol;
[0044] S4. Preparation of TiO2 / ZnO deposition cross-linked coated montmorillonite: 15 parts by weight of the cross-linked coated montmorillonite prepared in step S2 was added to 30 parts by weight of the Ti-Zn sol prepared in step S2, stirred and mixed for 15 minutes, heated to 105°C and dried for 1 hour, calcined at 400°C for 2 hours, and ball milled for 1 hour to obtain TiO2 / ZnO deposition cross-linked coated montmorillonite;
[0045] S5. Preparation of copper - silver ammonia complex ion solution: 5 parts by weight of copper chloride and 17 parts by weight of silver nitrate were dissolved in 100 parts by weight of water, and 22wt% ammonia solution was added dropwise until the precipitate just disappeared to obtain a copper - silver ammonia complex ion solution;
[0046] S6. Preparation of Ag / Cu metal particles fixed TiO2 / ZnO deposition cross-linked coated montmorillonite: add 10 parts by weight of the TiO2 / ZnO deposition cross-linked coated montmorillonite prepared in step S4 to 30 parts by weight of the copper-silver ammine ion solution prepared in step S5, add 5 parts by weight of glucose, heat to 85°C, stir to react for 1 hour, filter, wash, and dry to obtain Ag / Cu metal particles fixed TiO2 / ZnO deposition cross-linked coated montmorillonite;
[0047] S7. Preparation of antibacterial aluminum foil material: 12 parts by weight of polysiloxane, 1 part by weight of silane coupling agent, 4 parts by weight of Ag / Cu metal particles fixed TiO2 / ZnO deposited cross-linked coated montmorillonite obtained in step S6, 1 part by weight of additives and 30 parts by weight of organic solvent are mixed evenly to obtain an antibacterial coating, which is evenly spin-coated on aluminum foil to form an antibacterial layer with a thickness of 1.5 mm, heated to 100° C., and baked and cured for 1 hour to obtain an antibacterial aluminum foil material;
[0048] The silane coupling agent is a mixture of KH550 and KH602, with a mass ratio of 3:7;
[0049] The additives include dimethylpentylamide and hexadecyl alcohol in a mass ratio of 2:1.
[0050] Example 2
[0051] This embodiment provides a method for preparing an antibacterial aluminum foil material, which specifically includes the following steps:
[0052] S1. Pretreatment of montmorillonite: montmorillonite was added to a 4 mol / L sulfuric acid solution, stirred for 30 min, filtered, washed, and dried to obtain pretreated montmorillonite;
[0053] S2. Chitosan-alginate cross-linked coating: 12 parts by weight of chitosan were dissolved in 100 parts by weight of 1.5wt% hydrochloric acid solution, 30 parts by weight of the pretreated montmorillonite prepared in step S1 were added, stirred and mixed for 20 min, 10 parts by weight of alginate were added, stirred and reacted at 45 ° C for 60 min, filtered, washed, and dried to obtain a cross-linked coated montmorillonite;
[0054] S3. Preparation of Ti-Zn sol: 20 parts by weight of tetrabutyl titanate and 12 parts by weight of zinc acetate were dissolved in 100 parts by weight of a 70 wt% ethanol aqueous solution, the pH value of the solution was adjusted to 6, and the reaction was stirred for 60 min to obtain a Ti-Zn sol;
[0055] S4. Preparation of TiO2 / ZnO deposition cross-linked coated montmorillonite: 20 parts by weight of the cross-linked coated montmorillonite prepared in step S2 was added to 50 parts by weight of the Ti-Zn sol prepared in step S2, stirred and mixed for 15 minutes, heated to 110°C and dried for 2 hours, calcined at 600°C for 3 hours, and ball-milled for 2 hours to obtain TiO2 / ZnO deposition cross-linked coated montmorillonite;
[0056] S5. Preparation of copper - silver ammine ion solution: 7 parts by weight of copper sulfate and 20 parts by weight of silver nitrate were dissolved in 100 parts by weight of water, and 25wt% ammonia solution was added dropwise until the precipitate just disappeared to obtain a copper - silver ammine ion solution;
[0057] S6. Preparation of Ag / Cu metal particles fixed TiO2 / ZnO deposition cross-linked coated montmorillonite: add 15 parts by weight of TiO2 / ZnO deposition cross-linked coated montmorillonite prepared in step S4 to 40 parts by weight of the copper-silver ammine ion solution prepared in step S5, add 7 parts by weight of glucose, heat to 95°C, stir to react for 2h, filter, wash, and dry to obtain Ag / Cu metal particles fixed TiO2 / ZnO deposition cross-linked coated montmorillonite;
[0058] S7. Preparation of antibacterial aluminum foil material: 15 parts by weight of polysiloxane, 2 parts by weight of silane coupling agent, 6 parts by weight of Ag / Cu metal particles fixed TiO2 / ZnO deposited cross-linked coated montmorillonite obtained in step S6, 2 parts by weight of additives and 40 parts by weight of organic solvent are mixed evenly to obtain an antibacterial coating, which is evenly spin-coated on aluminum foil to form an antibacterial layer with a thickness of 1.5 mm, heated to 110°C, and baked for curing for 2 hours to obtain an antibacterial aluminum foil material;
[0059] The silane coupling agent is a mixture of KH550 and KH602, with a mass ratio of 5:7;
[0060] The additives include dimethylpentylamide and hexadecyl alcohol in a mass ratio of 3:2.
[0061] Example 3
[0062] This embodiment provides a method for preparing an antibacterial aluminum foil material, which specifically includes the following steps:
[0063] S1. Pretreatment of montmorillonite: montmorillonite was added to a 3 mol / L nitric acid solution, stirred for 25 min, filtered, washed, and dried to obtain pretreated montmorillonite;
[0064] S2. Chitosan-alginate cross-linked coating: 11 parts by weight of chitosan were dissolved in 100 parts by weight of 1.2wt% acetic acid solution, 27 parts by weight of the pretreated montmorillonite prepared in step S1 were added, stirred and mixed for 20 min, 7 parts by weight of alginate were added, stirred and reacted at 42 ° C for 55 min, filtered, washed, and dried to obtain a cross-linked coated montmorillonite;
[0065] S3. Preparation of Ti-Zn sol: 17 parts by weight of tetrabutyl titanate and 10 parts by weight of zinc acetate were dissolved in 100 parts by weight of a 60 wt% ethanol aqueous solution, the pH value of the solution was adjusted to 5.5, and the reaction was stirred for 50 min to obtain a Ti-Zn sol;
[0066] S4. Preparation of TiO2 / ZnO deposition cross-linked coated montmorillonite: 17 parts by weight of the cross-linked coated montmorillonite prepared in step S2 was added to 40 parts by weight of the Ti-Zn sol prepared in step S2, stirred and mixed for 15 minutes, heated to 107°C and dried for 1.5 hours, calcined at 500°C for 2.5 hours, and ball milled for 1.5 hours to obtain TiO2 / ZnO deposition cross-linked coated montmorillonite;
[0067] S5. Preparation of copper - silver ammonia complex ion solution: 6 parts by weight of copper nitrate and 18.5 parts by weight of silver nitrate were dissolved in 100 parts by weight of water, and 23.5wt% of ammonia water was added dropwise until the precipitate just disappeared to obtain a copper - silver ammonia complex ion solution;
[0068] S6. Preparation of Ag / Cu metal particles fixed TiO2 / ZnO deposition cross-linked coated montmorillonite: add 12 parts by weight of TiO2 / ZnO deposition cross-linked coated montmorillonite prepared in step S4 to 35 parts by weight of the copper-silver ammine ion solution prepared in step S5, add 6 parts by weight of glucose, heat to 90°C, stir to react for 1.5h, filter, wash, and dry to obtain Ag / Cu metal particles fixed TiO2 / ZnO deposition cross-linked coated montmorillonite;
[0069] S7. Preparation of antibacterial aluminum foil material: 13.5 parts by weight of polysiloxane, 1.5 parts by weight of silane coupling agent, 5 parts by weight of Ag / Cu metal particles fixed TiO2 / ZnO deposited cross-linked coated montmorillonite obtained in step S6, 1.5 parts by weight of additives and 35 parts by weight of organic solvent are mixed evenly to obtain an antibacterial coating, which is evenly spin-coated on aluminum foil to form an antibacterial layer with a thickness of 1.5 mm, heated to 105° C., and baked for curing for 1.5 hours to obtain an antibacterial aluminum foil material;
[0070] The silane coupling agent is a mixture of KH550 and KH602, with a mass ratio of 4:7;
[0071] The additives include dimethylpentylamide and hexadecyl alcohol in a mass ratio of 2.5:1.5.
[0072] Comparative Example 1
[0073] Compared with Example 3, the difference is that step S2 is not performed.
[0074] The details are as follows:
[0075] S1. Pretreatment of montmorillonite: montmorillonite was added to a 3 mol / L nitric acid solution, stirred for 25 min, filtered, washed, and dried to obtain pretreated montmorillonite;
[0076] S2. Preparation of Ti-Zn sol: 17 parts by weight of tetrabutyl titanate and 10 parts by weight of zinc acetate were dissolved in 100 parts by weight of a 60 wt% ethanol aqueous solution, the pH value of the solution was adjusted to 5.5, and the reaction was stirred for 50 min to obtain a Ti-Zn sol;
[0077] S3. Preparation of TiO2 / ZnO precipitated montmorillonite: 17 parts by weight of the pretreated montmorillonite obtained in step S1 was added to 40 parts by weight of the Ti-Zn sol obtained in step S2, stirred and mixed for 15 minutes, heated to 107°C and dried for 1.5 hours, calcined at 500°C for 2.5 hours, and ball-milled for 1.5 hours to obtain TiO2 / ZnO precipitated montmorillonite;
[0078] S4. Preparation of copper - silver ammonia complex ion solution: 6 parts by weight of copper nitrate and 18.5 parts by weight of silver nitrate were dissolved in 100 parts by weight of water, and 23.5wt% of ammonia water was added dropwise until the precipitate just disappeared to obtain a copper - silver ammonia complex ion solution;
[0079] S5. Preparation of Ag / Cu metal particles fixed TiO2 / ZnO precipitated montmorillonite: 12 parts by weight of the TiO2 / ZnO precipitated montmorillonite prepared in step S3 is added to 35 parts by weight of the copper-silver ammine ion solution prepared in step S4, and 6 parts by weight of glucose is added, and the mixture is heated to 90°C, stirred for reaction for 1.5 hours, filtered, washed, and dried to obtain Ag / Cu metal particles fixed TiO2 / ZnO precipitated montmorillonite;
[0080] S6. Preparation of antibacterial aluminum foil material: 13.5 parts by weight of polysiloxane, 1.5 parts by weight of silane coupling agent, 5 parts by weight of Ag / Cu metal particles fixed TiO2 / ZnO deposited montmorillonite obtained in step S5, 1.5 parts by weight of additives and 35 parts by weight of organic solvent were mixed evenly to obtain an antibacterial coating, which was evenly spin-coated on aluminum foil to form an antibacterial layer with a thickness of 1.5 mm, heated to 105° C., and baked for curing for 1.5 hours to obtain an antibacterial aluminum foil material;
[0081] The silane coupling agent is a mixture of KH550 and KH602, with a mass ratio of 4:7;
[0082] The additives include dimethylpentylamide and hexadecyl alcohol in a mass ratio of 2.5:1.5.
[0083] Comparative Example 2
[0084] Compared with Example 3, the difference is that tetrabutyl titanate is not added in step S3.
[0085] The details are as follows:
[0086] S3. Preparation of Zn sol: Dissolve 27 parts by weight of zinc acetate in 100 parts by weight of 60 wt% ethanol aqueous solution, adjust the pH value of the solution to 5.5, stir and react for 50 minutes to obtain Zn sol.
[0087] Comparative Example 3
[0088] Compared with Example 3, the difference is that zinc acetate is not added in step S3.
[0089] The details are as follows:
[0090] S3. Preparation of Ti sol: 27 parts by weight of tetrabutyl titanate were dissolved in 100 parts by weight of a 60 wt% ethanol aqueous solution, the pH value of the solution was adjusted to 5.5, and the reaction was stirred for 50 minutes to obtain Ti sol.
[0091] Comparative Example 4
[0092] Compared with Example 3, the difference is that steps S3 and S4 are not performed.
[0093] The details are as follows:
[0094] S1. Pretreatment of montmorillonite: montmorillonite was added to a 3 mol / L nitric acid solution, stirred for 25 min, filtered, washed, and dried to obtain pretreated montmorillonite;
[0095] S2. Chitosan-alginate cross-linked coating: 11 parts by weight of chitosan were dissolved in 100 parts by weight of 1.2wt% acetic acid solution, 27 parts by weight of the pretreated montmorillonite prepared in step S1 were added, stirred and mixed for 20 min, 7 parts by weight of alginate were added, stirred and reacted at 42 ° C for 55 min, filtered, washed, and dried to obtain a cross-linked coated montmorillonite;
[0096] S3. Preparation of copper - silver ammonia complex ion solution: 6 parts by weight of copper nitrate and 18.5 parts by weight of silver nitrate were dissolved in 100 parts by weight of water, and 23.5wt% of ammonia water was added dropwise until the precipitate just disappeared to obtain a copper - silver ammonia complex ion solution;
[0097] S4. Preparation of Ag / Cu metal particle fixed cross-linked coated montmorillonite: add 12 parts by weight of the cross-linked coated montmorillonite obtained in step S2 to 35 parts by weight of the copper-silver ammine ion solution obtained in step S3, add 6 parts by weight of glucose, heat to 90°C, stir to react for 1.5h, filter, wash, and dry to obtain Ag / Cu metal particle fixed cross-linked coated montmorillonite;
[0098] S5. Preparation of antibacterial aluminum foil material: 13.5 parts by weight of polysiloxane, 1.5 parts by weight of silane coupling agent, 5 parts by weight of Ag / Cu metal particles fixed cross-linked coated montmorillonite obtained in step S4, 1.5 parts by weight of additives and 35 parts by weight of organic solvent were mixed evenly to obtain an antibacterial coating, which was evenly spin-coated on aluminum foil to form an antibacterial layer with a thickness of 1.5 mm, heated to 105° C., and baked for curing for 1.5 hours to obtain an antibacterial aluminum foil material;
[0099] The silane coupling agent is a mixture of KH550 and KH602, with a mass ratio of 4:7;
[0100] The additives include dimethylpentylamide and hexadecyl alcohol in a mass ratio of 2.5:1.5.
[0101] Comparative Example 5
[0102] Compared with Example 3, the difference is that copper nitrate is not added in step S5.
[0103] The details are as follows:
[0104] S5. Preparation of silver ammine complex ion solution: 24.5 parts by weight of silver nitrate was dissolved in 100 parts by weight of water, and 23.5 wt% of ammonia water was added dropwise until the precipitate just disappeared to obtain a silver ammine complex ion solution.
[0105] Comparative Example 6
[0106] Compared with Example 3, the difference is that silver nitrate is not added in step S5.
[0107] The details are as follows:
[0108] S5. Preparation of copper ammine complex ion solution: 24.5 parts by weight of copper nitrate was dissolved in 100 parts by weight of water, and 23.5 wt% of ammonia water was added dropwise until the precipitate just disappeared to obtain a copper ammine complex ion solution.
[0109] Comparative Example 7
[0110] Compared with the embodiment 3, the difference is that steps S5 and S6 are not performed.
[0111] The details are as follows:
[0112] S1. Pretreatment of montmorillonite: montmorillonite was added to a 3 mol / L nitric acid solution, stirred for 25 min, filtered, washed, and dried to obtain pretreated montmorillonite;
[0113] S2. Chitosan-alginate cross-linked coating: 11 parts by weight of chitosan were dissolved in 100 parts by weight of 1.2wt% acetic acid solution, 27 parts by weight of the pretreated montmorillonite prepared in step S1 were added, stirred and mixed for 20 min, 7 parts by weight of alginate were added, stirred and reacted at 42 ° C for 55 min, filtered, washed, and dried to obtain a cross-linked coated montmorillonite;
[0114] S3. Preparation of Ti-Zn sol: 17 parts by weight of tetrabutyl titanate and 10 parts by weight of zinc acetate were dissolved in 100 parts by weight of a 60 wt% ethanol aqueous solution, the pH value of the solution was adjusted to 5.5, and the reaction was stirred for 50 min to obtain a Ti-Zn sol;
[0115] S4. Preparation of TiO2 / ZnO deposition cross-linked coated montmorillonite: 17 parts by weight of the cross-linked coated montmorillonite prepared in step S2 was added to 40 parts by weight of the Ti-Zn sol prepared in step S2, stirred and mixed for 15 minutes, heated to 107°C and dried for 1.5 hours, calcined at 500°C for 2.5 hours, and ball milled for 1.5 hours to obtain TiO2 / ZnO deposition cross-linked coated montmorillonite;
[0116] S5. Preparation of antibacterial aluminum foil material: 13.5 parts by weight of polysiloxane, 1.5 parts by weight of silane coupling agent, 5 parts by weight of TiO2 / ZnO deposited cross-linked coated montmorillonite prepared in step S4, 1.5 parts by weight of additives and 35 parts by weight of organic solvent were mixed evenly to prepare an antibacterial coating, which was evenly spin-coated on aluminum foil to form an antibacterial layer with a thickness of 1.5 mm, heated to 105° C., and baked for curing for 1.5 hours to obtain an antibacterial aluminum foil material;
[0117] The silane coupling agent is a mixture of KH550 and KH602, with a mass ratio of 4:7;
[0118] The additives include dimethylpentylamide and hexadecyl alcohol in a mass ratio of 2.5:1.5.
[0119] Comparative Example 8
[0120] Compared with Example 3, the difference is that no silane coupling agent is added in step S7.
[0121] Comparative Example 9
[0122] Compared with Example 3, the difference is that steps S3 to S6 are not performed.
[0123] The details are as follows:
[0124] S1. Pretreatment of montmorillonite: montmorillonite was added to a 3 mol / L nitric acid solution, stirred for 25 min, filtered, washed, and dried to obtain pretreated montmorillonite;
[0125] S2. Chitosan-alginate cross-linked coating: 11 parts by weight of chitosan were dissolved in 100 parts by weight of 1.2wt% acetic acid solution, 27 parts by weight of the pretreated montmorillonite prepared in step S1 were added, stirred and mixed for 20 min, 7 parts by weight of alginate were added, stirred and reacted at 42 ° C for 55 min, filtered, washed, and dried to obtain a cross-linked coated montmorillonite;
[0126] S3. Preparation of antibacterial aluminum foil material: 13.5 parts by weight of polysiloxane, 1.5 parts by weight of silane coupling agent, 5 parts by weight of cross-linked coated montmorillonite obtained in step S2, 1.5 parts by weight of additives and 35 parts by weight of organic solvent were mixed evenly to obtain an antibacterial coating, which was evenly spin-coated on aluminum foil to form an antibacterial layer with a thickness of 1.5 mm, heated to 105° C., and baked for curing for 1.5 hours to obtain an antibacterial aluminum foil material;
[0127] The silane coupling agent is a mixture of KH550 and KH602, with a mass ratio of 4:7;
[0128] The additives include dimethylpentylamide and hexadecyl alcohol in a mass ratio of 2.5:1.5.
[0129] Comparative Example 10
[0130] Compared with Example 3, the difference is that in step S7, no Ag / Cu metal particles are added to fix the TiO2 / ZnO deposition cross-linking and coating montmorillonite.
[0131] The details are as follows:
[0132] S7. Preparation of aluminum foil material: 18.5 parts by weight of polysiloxane, 1.5 parts by weight of silane coupling agent, 1.5 parts by weight of additives and 35 parts by weight of organic solvent were mixed to obtain an antibacterial coating, which was evenly spin-coated on an aluminum foil to form a coating with a thickness of 1.5 mm, heated to 105° C., and baked for 1.5 h to obtain an aluminum foil material;
[0133] The silane coupling agent is a mixture of KH550 and KH602, with a mass ratio of 4:7;
[0134] The additives include dimethylpentylamide and hexadecyl alcohol in a mass ratio of 2.5:1.5.
[0135] Test Example 1
[0136] The aluminum foil materials prepared in Examples 1-3 and Comparative Examples 1-10 were tested for antibacterial properties, and the minimum growth inhibition concentration (MIC) was obtained.
[0137] The results are shown in Table 1.
[0138] Table 1
[0139]
[0140] The minimum growth concentration indicates the minimum concentration of the antibacterial substance that inhibits microorganisms, and the unit ppm indicates the concentration in parts per million; the lower the concentration value, the better the antibacterial performance of the aluminum foil material. As can be seen from the above table, the antibacterial aluminum foil materials prepared in Examples 1-3 of the present invention have excellent antibacterial effects.
[0141] Test Example 2
[0142] The aluminum foil materials in Examples 1-3 and Comparative Examples 1-10 were spin-coated on both sides to prepare standard samples. The corrosion rate was measured by the immersion weight loss method. The samples were immersed in a 25°C solution with a mass fraction of 3.5% NaCl (pH=7). After immersion for 24 hours, the corrosion products on the surface of the material were removed, and the mass of the sample after drying was weighed. The mass change per unit area per unit time, i.e., the average corrosion rate v, was used to characterize the corrosion rate of the sample (mg·cm -1 ·h -1 ).
[0143] v=(w0-w1+w2) / St
[0144] Where, S-sample area (cm 2 ), t-corrosion time (h); w0-original mass of the sample (mg); w1-mass of the sample after the corrosion products are removed after the experiment (mg); w2-corrected weight loss of the blank sample of the same size and material when the corrosion products are removed (mg).
[0145] The results are shown in Table 2.
[0146] Table 2
[0147] Group <![CDATA[Corrosion rate (mg·cm -2 ·h -1 )]]> Example 1 0.009 Example 2 0.010 Example 3 0.007 Comparative Example 1 0.012 Comparative Example 2 0.034 Comparative Example 3 0.031 Comparative Example 4 0.045 Comparative Example 5 0.014 Comparative Example 6 0.013 Comparative Example 7 0.016 Comparative Example 8 0.065 Comparative Example 9 0.059 Comparative Example 10 0.082
[0148] It can be seen from the above table that the antibacterial aluminum foil materials prepared in Examples 1-3 of the present invention have good corrosion resistance.
[0149] Test Example 3
[0150] The aluminum foil materials prepared in Examples 1-3 of the present invention and Comparative Examples 1-10 were subjected to performance tests.
[0151] Adhesion test is carried out in accordance with GB / T9286-1998 (cut into 1mm square grids and test with 100 grids of adhesive tape);
[0152] The pencil hardness test is carried out in accordance with the standard of GB / T6739-2006 (Mitsubishi pencil at 45° angle, five times of defect judgment);
[0153] The wear resistance test was carried out in accordance with the standard of GB / T12721-2007 (using rubber, load 4.9N, 600 reciprocating frictions).
[0154] The results are shown in Table 3.
[0155] Table 3
[0156] Group Adhesion(grade) Pencil hardness (H) Wear resistance <![CDATA[Tensile strength (N / m 2 )]]> Example 1 0 6 Material not exposed 134 Example 2 0 6 Material not exposed 135 Example 3 0 7 Material not exposed 137 Comparative Example 1 1 6 Material not exposed 131 Comparative Example 2 0 6 Material not exposed 128 Comparative Example 3 0 6 Material not exposed 126 Comparative Example 4 0 5 A little exposed 119 Comparative Example 5 0 6 A little exposed 128 Comparative Example 6 0 6 A little exposed 127 Comparative Example 7 0 6 Partially exposed 122 Comparative Example 8 2 4 A little exposed 116 Comparative Example 9 1 5 A little exposed 113 Comparative Example 10 1 5 Partially exposed 110
[0157] It can be seen from the above table that the antibacterial aluminum foil materials prepared in Examples 1-3 of the present invention have good adhesion, hardness and wear resistance.
[0158] Test Example 4
[0159] The aluminum foil materials prepared in Examples 1-3 of the present invention and Comparative Examples 1-10 were placed at 60±5° C. and 70+5% humidity for 3 years, and then the antibacterial properties of the antibacterial aluminum foil were tested according to the requirements of GB / T 31402-2015.
[0160] The results are shown in Table 4.
[0161] The Escherichia coli was Escherichia coli ATCC25922.
[0162] The Staphylococcus aureus was Staphylococcus aureus ATCC29213.
[0163] Table 4
[0164]
[0165] It can be seen from the above table that the antibacterial aluminum foil materials prepared in Examples 1-3 of the present invention have good antibacterial durability.
[0166] Compared with Example 3, Comparative Example 1 is different in that step S2 is not performed. The antibacterial durability is significantly reduced and the adhesion is reduced. After the montmorillonite is acid-treated, the present invention further cross-links chitosan and alginate through a cross-linking reaction. The cations in the chitosan can attract each other with the anionic alginate to form a cross-linked structure, so that the carrier has a complex and multi-layer structure, which is not conducive to the large-scale and rapid release of silver ions and copper ions, and plays a certain sustained release effect, so as to facilitate the extension of the antibacterial time and the service life. The released metal ions will not cause toxicity. At the same time, the chitosan-alginate cross-linked structure formed also has good biological antibacterial performance, which can play a synergistic role and improve the mechanical properties, toughness, wear resistance and hardness of the aluminum foil.
[0167] Compared with Example 3, the difference between Comparative Examples 2 and 3 is that tetrabutyl titanate or zinc acetate is not added in step S3. Compared with Example 3, the difference between Comparative Example 4 and Example 3 is that steps S3 and S4 are not performed. Antibacterial properties are reduced, corrosion resistance is reduced, and mechanical properties are reduced. Ag, TiO2 and ZnO in the antibacterial layer of the present invention have photocatalytic effects. These metal ions with photocatalytic effects activate oxygen molecules in the water and air system to generate hydroxyl radicals (-OH) and active oxygen ions (O 2- ). Under the action of these strong oxidants, the structures of proteins, glycosides and other substances in bacteria are destroyed, and their normal metabolic functions are disturbed, so they cannot proliferate normally and eventually die, thus achieving the purpose of antibacterial and bactericidal. Among them, under the photocatalytic action of ZnO, the main active oxygen substance H2O2 can be produced, and H2O2 can react chemically with membrane proteins to kill bacteria. At the same time, the photocatalytic material in the present invention has a relatively high heat resistance and can adapt to some harsh and demanding environments. However, since its application scenario must be exposed to ultraviolet light and there must be water and oxygen, the present invention is also combined with other antibacterial materials to achieve synergistic antibacterial effects.
[0168] Compared with Example 3, the difference between Comparative Examples 5 and 6 is that copper nitrate or silver nitrate is not added in step S5. Compared with Example 3, the difference between Comparative Example 7 and Example 3 is that steps S5 and S6 are not performed. Antibacterial property and wear resistance are reduced. The reason why the antibacterial layer of the present invention usually causes the death of bacteria and viruses is that metal particles can release metal ions, such as Ag. + , Cu 2+, with positive charge, while the cell membrane of bacteria, viruses and other microorganisms has negative charge. Under the action of Coulomb attraction, the two are combined together, and the metal ions take the opportunity to pass through the cell membrane and enter the cell. The protein in the cell coagulates and loses its activity under the action of heavy metal ions. Therefore, the cell cannot produce synthase for synthesizing DNA, and the cell dies due to the destruction of its proliferation ability. After the microorganism loses its activity, the metal ions are freed and a new round of sterilization is carried out, and the long-term sterilization effect is achieved over and over again.
[0169] Compared with Example 3, Comparative Example 8 is different in that no silane coupling agent is added in step S7. The antibacterial property is reduced, the antibacterial durability is reduced, the corrosion resistance is reduced, and the adhesion and mechanical properties are reduced. The chitosan, oxides, etc. on the Ag / Cu metal particles fixed TiO2 / ZnO deposition cross-linked coated montmorillonite material of the present invention have a large number of hydroxyl structures, which are convenient for forming hydrogen bonds with silane coupling agents with amino groups, so that the organic and inorganic materials are stably composited to form a uniformly dispersed and uniform coating, so that the Ag / Cu metal particles fixed TiO2 / ZnO deposition cross-linked coated montmorillonite can be evenly and non-agglomerated spin-coated on the aluminum foil surface, while improving the adhesion performance of the coating on the aluminum foil surface, avoiding the problems of coating shedding and cracking, thereby exerting a stable antibacterial property.
[0170] Compared with Example 3, Comparative Example 9 is different in that steps S3 to S6 are not performed. The antibacterial property is reduced, the corrosion resistance is reduced, and the adhesion and mechanical properties are reduced. Compared with Example 3, Comparative Example 10 is different in that Ag / Cu metal particles are not added to fix TiO2 / ZnO deposition cross-linked coated montmorillonite in step S7. There is almost no antibacterial property, the corrosion resistance is reduced, and the adhesion and mechanical properties are reduced. It can be seen that Ag / Cu metal particles fix TiO2 / ZnO deposition cross-linked coated montmorillonite has a great influence on the antibacterial property and comprehensive performance of aluminum foil.
[0171] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an antibacterial aluminum foil material, characterized in that: The specific steps include: S1. Pretreatment of montmorillonite: adding montmorillonite to 2-4 mol / L nitric acid or sulfuric acid solution, stirring the reaction for 20-30 min, filtering, washing, and drying to obtain pretreated montmorillonite; S2. Chitosan-alginate cross-linked coating: 10-12 parts by weight of chitosan are dissolved in 100 parts by weight of 1-1.5wt% acetic acid or hydrochloric acid solution, 25-30 parts by weight of the pretreated montmorillonite prepared in step S1 are added, stirred and mixed uniformly, 5-10 parts by weight of alginate are added, the reaction is stirred at 40-45°C for 50-60min, filtered, washed, and dried to obtain a cross-linked coated montmorillonite; S3. Preparation of Ti-Zn sol: 15-20 parts by weight of tetrabutyl titanate and 7-12 parts by weight of zinc acetate are dissolved in 100 parts by weight of a 50-70wt% ethanol aqueous solution, the pH value of the solution is adjusted to 5-6, and the reaction is stirred for 40-60 minutes to obtain a Ti-Zn sol; S4. Preparation of TiO2 / ZnO deposition cross-linked coated montmorillonite: add 15-20 parts by weight of the cross-linked coated montmorillonite obtained in step S2 to 30-50 parts by weight of the Ti-Zn sol obtained in step S2, stir and mix evenly, heat to 105-110°C and dry for 1-2h, calcine at 400-600°C for 2-3h, and ball mill for 1-2h to obtain TiO2 / ZnO deposition cross-linked coated montmorillonite; S5. Preparation of copper - silver ammine ion solution: 5-7 parts by weight of a soluble copper salt and 17-20 parts by weight of silver nitrate are dissolved in 100 parts by weight of water, and 22-25wt% of aqueous ammonia is added dropwise until the precipitate just disappears to obtain a copper - silver ammine ion solution; S6. Preparation of Ag / Cu metal particles fixed TiO2 / ZnO deposition cross-linked coated montmorillonite: add 10-15 parts by weight of the TiO2 / ZnO deposition cross-linked coated montmorillonite obtained in step S4 to 30-40 parts by weight of the copper-silver ammine ion solution obtained in step S5, add 5-7 parts by weight of glucose, heat to 85-95°C, stir to react for 1-2h, filter, wash, and dry to obtain Ag / Cu metal particles fixed TiO2 / ZnO deposition cross-linked coated montmorillonite; S7. Preparation of antibacterial aluminum foil material: 12-15 parts by weight of polysiloxane, 1-2 parts by weight of silane coupling agent, 4-6 parts by weight of Ag / Cu metal particles fixed TiO2 / ZnO deposited cross-linked coated montmorillonite obtained in step S6, 1-2 parts by weight of additives and 30-40 parts by weight of organic solvent are mixed evenly to obtain an antibacterial coating, and the coating is evenly spin-coated on aluminum foil to form an antibacterial layer with a thickness of 1-2 mm, heated to 100-110° C., and baked and cured for 1-2 hours to obtain an antibacterial aluminum foil material; The silane coupling agent is a mixture of KH550 and KH602, with a mass ratio of 3-5:7; The additives include dimethylpentylamide and hexadecyl alcohol in a mass ratio of 2-3:1-2.
2. The preparation method according to claim 1, characterized in that: The soluble copper salt in step S5 is selected from at least one of copper chloride, copper sulfate and copper nitrate.
3. The preparation method according to claim 1, characterized in that: The organic solvent in step S7 is selected from at least one of ethyl acetate, methyl acetate, butyl acetate, acetone, methyl ethyl ketone, petroleum ether, ethyl ether, and ethanol.
4. An antibacterial aluminum foil material obtained by the preparation method according to any one of claims 1 to 3.
5. Use of the antibacterial aluminum foil material as claimed in claim 4 in packaging materials.
Citation Information
Patent Citations
Antibacterial polyester / aluminum foil composite packaging film and preparation method thereof
CN107379655A
Inorganic-organic composite antibacterial material being of three-dimensional reticular structure and preparation method
CN107517961A
Waterproof coating and preparation method thereof
CN115746707A